HUBUNGAN KOMPETENSI DAN MOTIVASI KERJA DENGAN KOMITMEN GURU MELAKSANAKAN TUGAS PENDIDIKAN AGAMA KRISTEN SEKABUPATEN TOBA SAMOSIR - Nimrod Limbong (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2021)
ABSTRACT This research aims to see connection between teacher competence and work motivation with commitment of religion teacher embraced with spreading questionnaires. Hypothesis tested in this research are: (1) There is relation of teacher’s competence with commitment of religion teacher to implement job. (2) There is connection between motivation of teaching occupation of religion teacher. (3). There is connection between mastery of competence by the teacher and motivation of teaching to occupation of religion teacher. This study use quantitative research method with the entire study population of teachers Pendidikan Agama Kristen (PAK) Kabupaten (Regency) Toba Samosir, amounting to 125 people and sample taken 30% of the total population of this study is that the sample as many 65 people. The research instrument is enclosed questionnaires, trials conducted questionnaires to 30 teachers PAK outside the sample. Validity and reliability of the instrument by using SPSS 22. Validity of the test result shown in the corrected item total correlation greater than r table at 0,374 and reliability test instrument with Alpha Formula obtained r11 = 0,0881 at the high category with such instrument valid and reliable. Data were analyzed using the following steps: 1) testing requirement analysis consisting of: (a) From the obtained value of normality test Sig. Shapiro-Wilk column. Test result above shows the value of competence (X1) = 0.05; Work motivation (X2) Of 0,063 and commitment Variable (Y) = 0. 292. These figures show that more than 0.05, then the data normal Distribution. b) obtained the probability of homogeneity test for the test Levena Sig.= 0.227 >0.05, then Ho is accepted, means there is no difference in variance between motivation and competence in running the task PAK commitment variable. This shows that the data variable duty commitment PAK homogeneity. 2) Hypothesis Testing consisting of: a) Competence to commitment correlation test shows the number 0,259. This relationship figure shows that there is correlation in the low category, competency with probabilities between task commitment PAK 0.037, 0.037 Figures < 0.05 means the two variables have a significant and purposeful relationship. b) correlation test was obtained that motivation to carry out the task PAK commitment rate was 0,642. This figure shows the correlations or relationship that is strong and direct. Probability between motivation and motivation to carry with 0,000 Commitment PAK task. Figures 0,000